Cross-Front Transport Triggered by Winter Storms Around the Shandong Peninsula, China - Xu, Xiaomei; Gao, Jianhua; Shi, Yong; Wu, Xiaodong; Lv, Jixuan; Zhang, Shuo; Liu, Shengjing; Liu, Tao; Yang, Guang (Frontiers in Marine Science, 2022)
Ocean fronts are widespread on the eastern China shelf, especially in winter and early spring. Previous studies have shown that sediments on the northern coast of the Shandong Peninsula could penetrate the coastal fronts and deposit on the southern coast of the Liaodong Peninsula, and this cross-front transport process is closely related to winter storms. However, the detailed mechanisms of cross-front transport remain unclear. In this study, through realistic numerical modeling and physical mechanism analysis, a dynamic mechanism involving cross-front transport triggered by winter storms was proposed, and two locations with the highest probability of frontal instability around the Shandong Peninsula were identified. In detail, forced by winter storms, the Lubei Coastal Current (LBCC) significantly intensifies first and causes frontal inertial instability in the early stage of the winter storm, favoring cross-front exchange between both sides of the front. Then, serving as a compensation current, the Yellow Sea Warm Current (YSWC) intensifies in the late stage of the winter storm, leading to the northward transport of the leaked materials. Furthermore, the intensity, distance, and path of the cross-front transport under varying winter storms are also investigated. This study provides a theoretical explanation for cross-front transport and analyzes the role of winter storms in it, providing some new ideas for nearshore materials dispersal to the sea, which is of great significance for future studies on pollutant diffusion, nutrient distribution, and sediment transport in coastal areas.